2022
DOI: 10.1186/s12903-022-02061-0
|View full text |Cite
|
Sign up to set email alerts
|

Online oral health information seeking experience and knowledge, attitudes and practices of oral health among iranian medical students: an online survey

Abstract: Background The internet is increasingly used as a source of health information. This study aimed to explore the online oral health information seeking experience, to determine the knowledge, attitudes and practices (KAP) of oral health, and to investigate the associations between online oral health information seeking experience and oral health KAP of participants. Methods A cross-sectional online survey was conducted. Three hundred and ninety-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…This paper describes online health informationseeking skills (OHISS) and its related factors in middle-aged people. Our study revealed that participants had a level of average the online health information-seeking skills which is similar to the studies conducted in other countries such as China and the United States [22][23][24]. In the country of Ghana, few patients use online health information [25].…”
Section: Discussionsupporting
confidence: 83%
“…This paper describes online health informationseeking skills (OHISS) and its related factors in middle-aged people. Our study revealed that participants had a level of average the online health information-seeking skills which is similar to the studies conducted in other countries such as China and the United States [22][23][24]. In the country of Ghana, few patients use online health information [25].…”
Section: Discussionsupporting
confidence: 83%
“…Four studies used in‐person questionnaires, 14 , 16 , 17 , 20 while the other six distributed online questionnaires among participants. 15 , 18 , 19 , 21 , 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
“… 14 , 17 , 18 , 19 , 20 , 22 , 23 However, in one study, participants revealed moderate attitudes toward online health information and online health experience sharing ( p < 0.05). 15 …”
Section: Resultsmentioning
confidence: 99%
“…The researchers used an online survey platform (Google Forms) to publish the questionnaire and generate the answer link for the respondents and distributed using the snowballing technique (Chen et al, 2021). The online survey was widely shared through social media, specifically the WhatsApp application (Bastani et al, 2022) based on its wide usage among the students.…”
Section: Methodsmentioning
confidence: 99%